All Days 2014
DOI: 10.2118/172329-ms
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Workflow for Assisted History Matching and Brownfield Design of Experiments for the Tengiz Field

Abstract: The main goal of history matching is to calibrate a reservoir model to production data and provide a model on which field development decisions can be made. Most of the history matching effort conducted in the industry is based on a single deterministic simulation model. With recent developments in probabilistic history matching techniques, faster computers, and efficient numerical algorithms, the opportunity to exploit these resources for efficient history matching workflows becomes available. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…By dividing the range of the attribute into intervals, the number of combinations among attributes increases significantly. One solution to this problem is to use sensitivity analyses to select the most influential attributes and reduce the search space (Almeida Netto et al, 2003;Rotondi et al, 2006;Kassenov et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By dividing the range of the attribute into intervals, the number of combinations among attributes increases significantly. One solution to this problem is to use sensitivity analyses to select the most influential attributes and reduce the search space (Almeida Netto et al, 2003;Rotondi et al, 2006;Kassenov et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Becerra et al (2011) used sensitivity analysis in an approach to reduce the uncertainty in a history matching problem. Kassenov et al (2014) showed an application of sensitivity analysis with design of experiments in the Tengiz field.…”
Section: Introductionmentioning
confidence: 99%